Pengaruh Permainan Tradisional Oray-orayan terhadap Keterampilan Sosial Anak - Lesi Oktiani Putri; Renata Nur Annisa; Yona Wahyuningsih (Journal on Education, 2023)
This paper is made to find out the effect of traditional oray-oryan games on children's social skills. This is motivated because with the advancement of technology, traditional games are starting to be forgotten. With technology, children will focus more on gadgets, laptops and other electronic devices. In addition, the level of addiction to modern games in children is also high so that it affects children's habits and behavior. This writing based on literature study describes the impact what happens to children when they are addicted to playing games which results in the character that will be awakened in children. In addition, this paper also examines the influence of traditional ory-orayan games on children's social skills